Relationship between Family Support and Student Career Decision Making in Vocational High School - Risma Dina; San Putra (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2022)
This study aims to determine the relationship between family support and student career decision making. This research was conducted at SMK Negeri 1 Binjai in class XI. This research includes quantitative research with correlational methods. The data collection technique is in the form of a questionnaire (questionnaire). The population of this study amounted to 266 students. The sample of this study amounted to 40 students. The sampling technique was done randomly. The results showed that from the results of the product moment correlation analysis hypothesis test of 0.942 > 0.312, it can be concluded that the null hypothesis (Ho) is rejected and (Ha) is accepted, it shows that there is a very strong relationship between family support and student career decision making.at SMK Negeri 1 Binjai.